New cross-rolling process for joining of hybrid components. Issue 1 (2020) - Brosius, Alexander; Guilleaume, Christina
Abstract: The proposed innovative cross-rolling process can be used to form hybrid components like shaft hub connections and electric drive parts. The advantages as well as the challenges are discussed in detail, especially the resulting notch geometry and possible approaches for mitigating adverse effects. While the shaft ideally should be a high strength steel, generally any other metal, ceramic or composite material can be used as a joining partner. This paper will present a numerical analysis of the joining process regarding work roll path and geometry as well as an experimental evaluation of the achievable properties and the resulting transmissible loads.